Pembuatan Bioplastik Berbahan Baku Limbah Organik dengan Penambahan Tepung Tapioka dan Gliserol - Sri Widyastuti; Rhenny Ratnawati; Nurmasyta Sylviana Priyono (Graduate School Bogor Agricultural University (SPs IPB), 2021)
Bioplastic is a plastic that can be decomposed because it can return to nature. This study aims to examine the optimal composition for the of bioplastics with various compositions of raw material. Comparison of the composition of waste banana peel:tapioca flour:glycerol, respectively 1:10:7,5 (sample A) and 1:13:11,25 (sample B). The ratio of the composition of waste rice:tapioca flour:glycerol in sample C and D is 1:10:7,5 and 1:13:11,25, respectively. Bioplastics are processed by using a composite of banana peel or rice waste which is dried to a moisture content of 70%. 30 mL of distilled water was added to the bioplastic and heated until thickened. The bioplastic is molded in a baking sheet while it is still hot and in an oven at 117˚C, then cooled at room temperature. The optimal composition of bioplastic is found in sample B with a biodegradation test value of 58% and contains bioplastics with functional groups O-H, C-H, C=O, C=C, C-O and =C-H in the FTIR test results. The quality standard values ​​for the tensile strength test and elongation test at break in sample B have values ​​of 10.9 MPa and 29%, respectively.